A New Species of the Mexican Tillandsia erubescens Group (Bromeliaceae) - Granados Mendoza, Carolina; Salazar, Gerardo A.; Flores-Cruz, María (Phytotaxa, 2016)
The Tillandsia erubescens group (Bromeliaceae) encompasses seven currently recognized species with reduced, pendulous inflorescences and endemic to pine-oak forests in the high mountains of Mexico. During the course of a taxonomic revision based on extensive study of herbarium specimens and detailed observations in the field, a new species of this group was discovered, which is described and illustrated here as T. tecolometl. The new entity belongs to a subgroup of species with purple corollas that also includes T. andrieuxii, T. macdougallii, T. oaxacana and T. pseudooaxacana. We present detailed morphological comparisons of the new species to the other species in the group with purple corollas, complemented with information on their habitat preferences, geographical distribution and phenology. An identification key to all the species with purple corollas belonging to the Tillandsia erubescens group is provided.